2022
DOI: 10.3389/fmicb.2021.820380
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Aspergillus niger for Efficient Fatty Acid Ethyl Ester Synthesis in Aqueous Phase and the Molecular Mechanism

Abstract: Fatty acid ethyl esters are important flavor chemicals in strong-flavor baijiu. Microorganisms are the main contributors to ester synthesis during baijiu manufacture. However, the ester synthesis was unstable between batches. This was owing to a limited knowledge of the mechanisms for ester synthesis by microorganisms. In this work, a fatty acid ethyl ester synthesizing Aspergillus niger strain CGMCC (China General Microbiological Culture Collection) 3.4309 was identified. The conversion ratios of ethyl valera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…However, in the study of southern Chinese high-temperature Daqu, the predominant genus of WQ was Bacillus [48]. Bacillus and Aspergillus were the main microbial genera in various types of Daqu, which could produce a variety of flavor precursors and substances; especially important are contributions to the production of pyrazines [15,53,54]. Interestingly, the correlational heatmap analysis showed that Bacillus and Aspergillus had no significant correlation with tetramethylpyrazine.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the study of southern Chinese high-temperature Daqu, the predominant genus of WQ was Bacillus [48]. Bacillus and Aspergillus were the main microbial genera in various types of Daqu, which could produce a variety of flavor precursors and substances; especially important are contributions to the production of pyrazines [15,53,54]. Interestingly, the correlational heatmap analysis showed that Bacillus and Aspergillus had no significant correlation with tetramethylpyrazine.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, enzymatic ester bond synthesis and hydrolysis could be applied in many aspects besides plastic industry, such as the traditional fermented food industry. Ester bond synthesis or hydrolysis by enzymes played a crucial role on formation of flavor esters and degradation of potential harmful esters, thus greatly improved product quality (Xu et al, 2020(Xu et al, , 2021a(Xu et al, , 2023Zhao et al, 2023). In short, enzymatic ester bond synthesis and hydrolysis is a research hot topic worth continuous studies.…”
Section: Sequences Structures and Properties Of Enzymes For Paes Hydr...mentioning
confidence: 99%
“…Esters are important aromatic substances in baijiu. A large number of studies have found that various strains such as Aspergillus niger and Rhizopus have a strong ability to catalyze the production of fatty acid ethyl ester ( Xu et al, 2021a ). It was also found that Daqu is a saccharification agent and starter for brewing different types of baijiu.…”
Section: Formation Of Flavor Substances In Baijiumentioning
confidence: 99%